Information–Movement Coupling in The Control of Driver Approach to an Intersection. Issue 4 (2nd October 2017) - Mathieu, Julie; Bootsma, Reinoud J.; Berthelon, Catherine; Montagne, Gilles
ABSTRACT: We characterized the control mechanisms underlying crossing an intersection with vehicular traffic. Specifically, we identified potential markers of the coupling between information and movement through a kinematic analysis of the approach. We exposed participants in a driving simulator experiment to several scenarios. We manipulated task constraints by varying the acceleration capabilities of the vehicle and the time available to make speed adjustments. The results highlighted gradual, systematic adjustments, which make it possible to cross the intersection in a zone that is close to the center of the intervehicular gap. The functional nature of these adjustments was highlighted by concomitant and opposite variation in the variability of current speed and current deviation. In all cases, an increase in the standard deviation of speed was accompanied by a reduction in the standard deviation of current deviation. Neither time to make adjustments nor acceleration capabilities modified the observed kinematic patterns, but they did modulate the adjustments that were produced. Overall, these results were consistent with a control mechanism based on the implementation of an information–movement cycle.